ẢNH HƯỞNG CỦA POLYME SIÊU HẤP THỤ NƯỚC ĐẾN SỰ SINH TRƯỞNG, PHÁT TRIỂN CỦA CÁC LOÀI CÂY HỌ ĐẬU TRỒNG TRÊN BÃI THẢI KHAI THÁC THAN – MỎ THAN NÚI HỒNG - TỈNH THÁI NGUYÊN - Khôi, Nguyễn Văn; Thiệp, Thân Văn; Công, Trịnh Đức; Thắng, Trịnh Vũ; Hà, Phạm Thị Thu (Vietnam Journal of Science and Technology, 2012)
THE EFFECT OF SUPER WATER ABSOBENT POLYMER ON THE GROWTH AND DEVELOPMENT OF GREEN MARUNE CROPS ON A SPOIL DUMP OF NUI HONG COAL MINE IN THAI NGUYEN PROVINCE Experimental models applying water super absorbent polymer to plant some green manure crops were carried out in the spoil dump of the III lenticular coal bed of Nui Hong coal mine in Thai Nguyen province. Theprosia, Wedelia trilobata, Mucuna benettii, Pueraria lobata were selected for studying. The effect of AMS-1 on some factors of their growth and development were observed. The results showed that there were significant differences between models with and without AMS-1. After 12 months, survival proportion, yield of living mass, soil cover proportion of the models using AMS-1 were higher than those of the models without AMS-1. Simultaneously, the fertility of the soil increased significantly after experimenting.